PEMANFAATAN MEDIA LINGKUNGAN ALAM DALAM PEMBELAJARAN BAHASA UNTUK MENINGKATKAN KREATIVITAS ANAK USIA 5-6 TAHUN DI PAUD - Sumarni, RR. Anik; Astuti, Indri; Mering, Aloysius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to describe  the using of nature  environment Media in language learning to increase the  creativity of children 5-6 years old at PAUD Terpadu Negeri Pembina Ketapang. This research use qualitative approach. The subjects of research  are teachers, children, and children parents. Data is collected by watching or  observing, interview and study document. Checking data validity is done by observing dilligently and triangulation. The result of this research shows that the using of environment media has been used by the teacher in language learning at PAUD Terpadu Negeri Pembina Ketapang. The using of  nature environment media is able to build children creativity 5-6 years old and is able to create joyful learning. Children are able to develope speaking creatively by asking, expressing their feeling, and tell the story. Keywods:  nature environment media , language creativity